Analisis Risiko Kualifikasi Pemasok dan Pendekatan Mitigasi Risikonya dalam Manajemen Rantai Pasok Industri Farmasi - Ella Fazila; Sandra Megantara; Gracia Anastasya (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Pharmaceutical products play a crucial role in supporting medical interventions to prevent, treat, and cure diseases, making their availability and quality key factors in healthcare services. Therefore, the pharmaceutical supply chain must ensure the availability of medicines in adequate quantities and meet quality standards. Supplier qualification is a critical step in supply chain management aimed at ensuring quality, sustainability, and compliance with regulations. This article analyzes the main risks in the supplier qualification process, such as quality risks, compliance risks, and supply disruptions. Risk mitigation strategies, such as regular audits, source diversification, and the implementation of digital technologies, play an important role in enhancing the efficiency, flexibility, and sustainability of the pharmaceutical supply chain, thereby supporting the competitiveness of the industry in consistently meeting market demands and complying with stringent regulatory standards. Through this research, it is hoped that strategic guidelines can be produced to improve the efficiency of pharmaceutical supply chain risk management, resulting in a positive impact on the overall healthcare system.